Afro-Catholic festivals in the Americas: performance, representation, and the making of Black Atlantic tradition - Fromont, Cécile (Africana religions, 2019)
Sangamentos on Congo Square : Kongolese warriors, brotherhood kings, and Mardi Gras Indians in New Orleans / Jeroen Dewulf -- Moros e Christianos ritualized naval battles : baptizing American waters with African spiritual meaning / Kevin Dawson -- A Mexican sangamento : the first Afro-Christian performance in the Americas / Miguel A. Valerio -- Representing an African king in Brazil / Lisa Voigt -- Black ceremonies in perspective : Brazil and Dahomey in the eighteenth century / Junia Ferreira Furtado -- Envisioning Brazil's Afro-Christian congados : the black king and queen festival lithograph of Johann Moritz Rugendas / Cécile Fromont -- The Orisa house that Afro-Catholics built : Africana antecedents to Yoruba religious formation in Trinidad / Dianne M. Stewart -- On hearing Africas in the Americas : domestic celebrations for Catholic saints as Afro-diasporic religious tradition / Michael Iyanaga.